2011
DOI: 10.1063/1.3641421
|View full text |Cite
|
Sign up to set email alerts
|

Rectifying and negative differential resistance behaviors of a functionalized Tour wire: The position effects of functional groups

Abstract: Based on Tour wire, we construct four D-π-A molecular devices with different positional functional groups, in an attempt to explore the position effects of functional groups on their electronic transport properties and to show that some interesting physical phenomena can emerge by only varying the position of functional groups. The first-principles calculations demonstrate that the position of functional groups can affect the rectifying behaviors (rectification direction and ratio) significantly and determines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…They investigated the rectification mechanism through a donor-σ bridge-acceptor wire and found rectifying properties in a direction opposite to the one proposed by the Aviram–Rathner rectification mechanism . Negative differential resistance was estimated in asymmetrically substituted and asymmetrically coupled to the electrodes Tour wires . Novel donor-π bridge-acceptor wires were suggested that show rectifying ratios close to 10 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They investigated the rectification mechanism through a donor-σ bridge-acceptor wire and found rectifying properties in a direction opposite to the one proposed by the Aviram–Rathner rectification mechanism . Negative differential resistance was estimated in asymmetrically substituted and asymmetrically coupled to the electrodes Tour wires . Novel donor-π bridge-acceptor wires were suggested that show rectifying ratios close to 10 .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…NDR has very important applications in electronic devices including amplier, memory, and fast switch. Possible mechanisms have been proposed theoretically [30][31][32][33][34] and experimentally. 35 However, the mechanism of NDR is still under debate.…”
Section: Resultsmentioning
confidence: 99%
“…Several propositions have been made so far on CC rec-tification, but too limited works are available on SC rectification which thus certainly demands critical analysis to probe into it further. For purposeful designing of a rectifier we need to focus not only on how to achieve higher rectification ratio [1][2][3][4][5][6][7][8][9][12][13][14][15] , but at the same time emphasis should be given on how its magnitude and direction can be controlled selectively [16][17][18][19] . The present work essentially focuses on all these issues.…”
Section: Introductionmentioning
confidence: 99%